Pemberdayaan UMKM Rengginang Desa Dolok Kahean melalui Transformasi Digital - Muhammad Fawaz Elfikri; Salman Nasution (Lembaga Pengembangan Kinerja Dosen, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a very important and strategic role in supporting the overall economic structure, with a contribution of 61.97% to the country's Gross Domestic Product (GDP). However, MSMEs, especially in rural areas, still face fundamental challenges, such as a lack of understanding and implementation of modern marketing and digital technologies. This service focuses on strategic efforts to empower Rengginang Ibu Saliem MSMEs in Dolok Kahean Village through a digital transformation program. The method used is descriptive qualitative Action Research, designed for direct program implementation and evaluation. The results of the pre-intervention showed that there was a severe digital gap in Rengginang products, although they had a tested taste, but still relied on traditional marketing models. Strategic intervention is carried out through two main pillars, namely, branding optimization by creating the trademark